Development of a discrete event simulation model for cave mining ore handling systems with open source tools - Silva, DA (MassMin 2020: Proceedings of the Eighth International Conference & Exhibition on Mass Mining, 2020)
The ore handling systems represent one of the largest expenses in cave mining, while the productivity and cost of a given production system can significantly impact the value of mining projects and operations. Moreover, in recent years the increase in mineral production using mass mining methods has led to significant progress in extraction techniques as well as equipment and technologies. Simulations are used to mimic real situations of production systems to aid in the design of new concepts and make engineered decisions. Discrete event simulation (DES) techniques can be applied to a wide range of analyses in cave mining, from refinement of cost and feasibility of plans or schedules to understanding the system behaviour for better decisions before expenses. This paper discusses the foundations to build a simulation model, while presenting the development of a discrete event simulation code using the R-Simmer package for the R language, to estimate productivity and capacity of an underground mining production system. Models using open source tools are intended to be an alternative to commercial simulation software, which can be onerous and restricted to specific settings. The outcome of this work constitutes a novel contribution to the simulation field, with the benefit to help design and assess cave mining ore handling systems but also create the basis of a future fully open-source simulation tool for cave mining.